ASSESSMENT OF NUTRITIONAL STATUS OF SCHOOL CHILDREN IN PUBLIC AND PRIVATE SECTOR SCHOOLS BY ANTHROPOMETRY - Sana Zahid; Zahid Masood; Rumsha Fayyaz et al. (Journal of University Medical & Dental College, 2017)
ABSTRACT: BACKGROUND: Malnutrition is globally increasing public health concern among children and Pakistan is no exception. Malnutrition has led to growing problems of morbidity and mortality. Children are an asset to their nation and their health is integral for the progress of any country. OBJECTIVE: Study was designed to evaluate the nutritional status of primary schools going children o f government and private schools in urban area. MATERIAL & METHODS: The study was conducted from Feb 2017 to March 2017. Two hundred primary school children were randomly selected out of which 100 were taken from government and private sector school each from urban area of Faisalabad. The comparative cross sectional study was carried out in primary school going children and nutritional status was interpreted using CDC growth curves and z scores were evaluated for stunting, wasting and thinness through WHO criteria. RESULTS: The percentage of stunted children was 25.5% and of this proportion, 71.6% belonged to government school. 20% children were found to be suﬀering from wasting out of which 57.1% belonged to government school. It was observed that the students from the government school had a slightly higher percentage of students with a normal BMI (56%) as opposed to the students of private school at 54%. There were more underweight students in government school than in private school (69.8% and 30.2% respectively). 64% of the overweight students belonged to private school. The proportion of obese students was found to be highest in private school (94.7%). CONCLUSION: A signiﬁcant number of students had malnutrition in the form of stunting and wasting both in government and private sector schools under study. Socio economic status directly aﬀected nutritional status.